Oil–Water Separation Polypropylene Foam with Advanced Solvent-Evaporation Induced Coexistence of Microspheres and Microporous Structure - Wang, Xin; Zhang, Mingtao; Schubert, Dirk W.; Liu, Xianhu (Macromolecular Rapid Communications, 2022)
For decades, crude oil spills and oil wastewater have become the most problematic environmental pollution and damage to public health. Therefore, it is considerable to develop superhydrophobic polymer foam for separating oil from water with high selectivity and sorption capacity. Here, a new type of environmentally friendly pure polypropylene (PP) foam with superhydrophobicity is first time proposed with a particular coexistence of microspheres and microporous structure fabricated via an advanced solvent-evaporation method. The PP foam exhibits exceptional superhydrophobic with a water contact angle of 151° and the maximum saturated adsorption capacity of 26 g g−1. After more than 15 h of cyclic continuous oil–water pumping experiment, it still maintains a high oil absorption efficiency of 98%, providing the basis for practical commercial applications. More importantly, the variation of hydrophobic properties is described by Flory–Huggins polymer solution theory and Huggins interaction parameters, and the optimal solution ratio range is predicted which provides a relevant theoretical basis for actual industrial production.
CRIS-Team Scopus Importer:2022-04-22
Keywords: microporous structures; microspheres; oil–water separation; polypropylene; superhydrophobic materials